Honeybee : the busy life of Apis mellifera - Fleming, Candace; Rohmann, Eric (2019)
Describes the life cycle of the hard-working honeybee
Illustrations rendered in oil paints
Includes bibliographical references (page [43])
Ages 6-9
Keywords: Honeybee -- Juvenile literature; Honeybee -- Behavior -- Juvenile literature; Honeybee -- Life cycles -- Juvenile literature; Instructional and educational works; Creative nonfiction; Picture books